2019
DOI: 10.1021/acssuschemeng.8b04809
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Hybrid Zinc-Based Materials from Ionic Liquids: A Novel Route to Prepare Active Zn Catalysts for the Photoactivation of Water and Methane

Abstract: A new and simple route for the preparation of zincbased materials is proposed in this work. The synthesis of zinc oxide from the hydrolysis of imidazolium trichlorozincate ionic liquids (ILs) produces catalytic active nanostructured materials, where the size and shape (irregular particles, nanorods) are dependent on the synthetic conditions employed. Indeed, the hydrolysis of trichlorozincate ILs prepared by an equimolar ionic liquid:ZnCl 2 ratio afforded irregular particles, while increasing the IL amount (2:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…[17][18][19] The great variety of preparation routes under development attests to the need to find facile, inexpensive, environmentally-benign, and scalable fabrication strategies whilst maintaining morphological control and uniformity, good throughput and high yields for large-scale synthesis of these nanomaterials. To overcome the challenges faced by large scale production of ZnO nanoparticles, two interesting approaches have been recently explored, firstly Zn foils as a better starting material [20][21][22][23] and secondly ILs as solvent, [24][25][26][27][28] though not in combination. With the latter, synthesis of ZnO has either been achieved by using a IL containing Zn 24,25 or a Zn containing salt dissolved in solution, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] The great variety of preparation routes under development attests to the need to find facile, inexpensive, environmentally-benign, and scalable fabrication strategies whilst maintaining morphological control and uniformity, good throughput and high yields for large-scale synthesis of these nanomaterials. To overcome the challenges faced by large scale production of ZnO nanoparticles, two interesting approaches have been recently explored, firstly Zn foils as a better starting material [20][21][22][23] and secondly ILs as solvent, [24][25][26][27][28] though not in combination. With the latter, synthesis of ZnO has either been achieved by using a IL containing Zn 24,25 or a Zn containing salt dissolved in solution, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This high activity can be related to the large surface‐to‐volume ratio of the nanostructured materials and the presence of residual IL and HCl at the particle's surface, which can influence the photodegradation process. Indeed, previous studies from our group showed that the IL generates hydrophilic zones at the semiconductor surface, which may facilitate the approach of polar molecules [8a,13] . Moreover, it was reported that the imidazolium cation can also trap and transfer the photogenerated electrons, which may facilitate the formation of the hydroxyl radical and accelerate the degradation of dyes [14] .…”
Section: Resultsmentioning
confidence: 97%
“…Theg enerated holes with their mild oxidizing ability promote the activation of CH 4 molecules and inhibit TOM, leading to the high selectivity of the C 2 hydrocarbons.Souza et al applied aZnO nanocluster imidazolium trichlorozincate wrapped in ionic liquids (ILs) as the catalyst for the photocatalytic OCM-O 2 under irradiation with aX el amp under ambient conditions. [101] Ah igh production rate of 787 mmol g À1 h À1 for C 2 H 6 is achieved at an optimal CH 4 /O 2 pressure ratio of 5:1, and the selectivity for C 2 H 6 is about 93 %(Figure 16 b).…”
Section: Photocatalytic Oxidative Coupling Of Methane (Ocm)mentioning
confidence: 99%
“…Oxygen is anonmetallic oxidant with ahigh reactivity and low toxicity that possesses the ability to readily form various oxides with most elements and compounds.Oxygen is widely used as the oxidant in av ariety of oxidation reactions, including the photooxidation of methane. [20,21,26,30,31,36,55,[101][102][103][104] Themain reactions of the methane-oxygen system are TOM and POM. TOM offers the possibility of efficiently removing trace amounts of methane,while POM offers an eco-friendly way to produce syngas,C 2 hydrocarbons,a nd oxygenates at RT and ambient pressure.…”
Section: Methane-oxygen Systemmentioning
confidence: 99%